Review of The Structure of The Bored Pile and Pile CAP The Premiere MTH Project - Kuncara, Eksa Anjar (Journal of Global Engineering Research and Science, 2023)
The Premiere MTH is an apartment complex located in South Jakarta, constructed on land with a hard soil layer extending deeper than 16 meters. Given these conditions, a bored pile foundation was selected as the optimal solution. This foundation type can be tailored to the necessary depth while minimizing disruption to nearby structures during installation. A bored pile is a type of deep foundation created by drilling into the ground to a specified depth. The process involves drilling a hole with specialized equipment, inserting a steel reinforcement cage, and then pouring concrete into the hole. Special tools are used to lift and position the casing and reinforcement. Once the concrete is poured, the casing is removed. According to the design analysis, the bored pile foundations used in this project have a diameter of 800 mm, with varying depths of 30 m and 35 m.